2017
DOI: 10.1038/pr.2017.70
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between maternal caffeine intake during pregnancy and CYP1A2 C164A polymorphism affects infant birth size in the Hokkaido study

Abstract: Background: Caffeine, 1,3,7-trimethylxanthine, is widely consumed by women of reproductive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
2
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 46 publications
2
31
2
8
Order By: Relevance
“…Coffee drinking is beneficial when we drink in moderation 2-4 cup per day it has a negative effect on our health when we drink more than considerable range [1]. Also, Nonsmokers who rapidly metabolize caffeine may be at increased risk for having infants with decreased birth size when consuming ≥ 300 mg of caffeine per day [74].…”
Section: Health Risks Of Coffee Consumptionmentioning
confidence: 99%
“…Coffee drinking is beneficial when we drink in moderation 2-4 cup per day it has a negative effect on our health when we drink more than considerable range [1]. Also, Nonsmokers who rapidly metabolize caffeine may be at increased risk for having infants with decreased birth size when consuming ≥ 300 mg of caffeine per day [74].…”
Section: Health Risks Of Coffee Consumptionmentioning
confidence: 99%
“…Nehlig Japanese study (Sasaki et al, 2017). This association might help understanding the inconsistent effects observed on the fetus after caffeine consumption.…”
mentioning
confidence: 95%
“…Notably, caffeine's effects on pregnancy outcomes have been shown to be highly variable between individuals in both rodents [35,38] and humans [5,8,9,45,46] (Figure 2A). Substantial interindividual phenotypic variation and the underling mechanism(s) in complex traits and diseases have become an area of significant scientific interest over the past two decades.…”
Section: Interindividual Variation In Caffeine Responsementioning
confidence: 99%
“…in caffeine metabolism, represents a well-studied example ( Figure 2B and Box 1). Epidemiological studies have found that when exposed to the same dosages of caffeine, women with higher CYP1A2 enzyme activity (rapid caffeine metabolism) have an increased risk of pregnancy disorders compared to those with lower CYP1A2 enzyme activity [5,8,9,45,46]. Human CYP1A2 mRNA levels represent more than 40-fold interindividual differences, and the in vivo activity of the CYP1A2 enzyme varies up to 60-fold, as probed by the 3-demethylation of caffeine [49].…”
Section: Interindividual Variation In Caffeine Responsementioning
confidence: 99%
See 1 more Smart Citation